Association between fast-food consumption and lifestyle characteristics in Greek children and adolescents; results from the EYZHN (National Action for Children's Health) programme. Issue 18 (16th October 2018) - Tambalis, Konstantinos D; Panagiotakos, Demosthenes B; Psarra, Glyceria; Sidossis, Labros S
Abstract: Objective: To examine the prevalence of fast-food consumption and the association between fast food and lifestyle factors in a representative sample of children and adolescents. Design: Cross-sectional, observational study. Fast-food consumption and dietary habits were evaluated using questionnaires (KIDMED index). Anthropometric and physical fitness measurements were obtained by trained investigators. Physical activity (PA) status, sedentary activities and sleeping habits were assessed through self-completed questionnaires. Setting: Greece. Subjects: Population data derived from a school-based health survey (EYZHN programme) carried out in 2015 on 177 091 (51 % boys) children aged 8–17 years. Results: A greater proportion of boys v . girls (23·3 v . 15·7 %, P <0·001) and of adolescents v . children (26·9 v . 17·1 %, P <0·001) reported they consume fast foods >1 time/week. Frequent fast-food consumption was strongly correlated with unhealthy dietary habits such as skipping breakfast and consuming sweets/candy regularly. Adjusting for several covariates, insufficient dietary habits, insufficient (<8–9 h/d) sleep, inadequate PA levels and increased screen time increased the odds (95 % CI) of being a frequent fast-food consumer by 77 % (0·218, 0·234), 30 % (1·270, 1·338), 94 % (1·887, 1·995) and 32 % (1·287, 1·357), respectively. Being overweight/obese or centrally obese did not correlate with frequency of fast-food consumption. Conclusions: Frequent fast-food consumption was associated with an unhealthy lifestyle profile among children and adolescents. The findings support the development of interventions to help children adopt healthier dietary habits.